Semiconductor nanochannels in metallic carbon nanotubes by thermomechanical chirality alteration - Tang, Dai-Ming; Erohin, Sergey V.; Kvashnin, Dmitry G.; Demin, Victor A.; Cretu, Ovidiu; Jiang, Song; Zhang, Lili; Hou, Peng-Xiang; Chen, Guohai; Futaba, Don N.; Zheng, Yongjia; Xiang, Rong; et al. (Science (American Association for the Advancement of Science), 2021)
The use of carbon nanotubes (CNTs) as short-channel-length transistors will require control of their chirality, which determines whether they are semiconducting or metallic and if they form strong, low-resistance contacts. Tang et al . fabricated CNT intramolecular transistors by progressive heating and straining of individual CNTs within a transmission electron microscope. Changes to chirality along sections of the nanotube created metallic-to-semiconducting transitions. A semiconducting nanotube channel was covalently bonded to the metallic nanotube source and drain regions. The resulting CNT intramolecular transistors had channel lengths as short as 2.8 nanometers. —PDS Strain and heating of carbon nanotubes in a transmission electron microscope created internal metal-semiconductor junctions. Carbon nanotubes have a helical structure wherein the chirality determines whether they are metallic or semiconducting. Using in situ transmission electron microscopy, we applied heating and mechanical strain to alter the local chirality and thereby control the electronic properties of individual single-wall carbon nanotubes. A transition trend toward a larger chiral angle region was observed and explained in terms of orientation-dependent dislocation formation energy. A controlled metal-to-semiconductor transition was realized to create nanotube transistors with a semiconducting nanotube channel covalently bonded between a metallic nanotube source and drain. Additionally, quantum transport at room temperature was demonstrated for the fabricated nanotube transistors with a channel length as short as 2.8 nanometers.